Kovalius—a new genus of cave-dwelling harvestmen from the Caucasus (Opiliones: Sclerosomatidae: Leiobuninae) - Tchemeris, Aleksey N. (Zootaxa, 2023)
A new genus Kovalius gen. nov. and species K. logunovi sp. nov., are described from the Sokolova Cave of NW Caucasus, Russia. This is the second genus and third species within Leiobuninae recorded from caves in the NW Caucasus, Sochi Region. A close relationship between Kovalius and Nelima Roewer, 1910 is discussed based on presence in Kovalius of a distinctly developed and pronounced inner patellar apophysis exceeding half of the length on the patellae on the pedipalps and unusual structure of the penis. In this paper, Kovalius is diagnosed, the male K. logunovi sp. nov. is described and illustrated, and the only known locality of the species is mapped.